Directed differentiation of human pluripotent stem cells into epidermal keratinocyte-like cells - Gowher Ali (14152593) (2022)
The human pluripotent stem cell (hPSC) differentiation has allowed for the generation of in vitro models to study human diseases in a dish. This protocol describes the generation of keratinocyte-like cells from hPSCs in chemically defined media. Treating hPSCs with retinoic acid and BMP4 induced the generation of keratinocyte progenitors, which further differentiated into mature keratinocytes in the presence of calcium. The keratinocytes generated with this protocol could be used to study keratinocyte biology, drug screening, and skin-related diseases. For complete details on the use and execution of this protocol, please refer to Ali et al. (2020). Other Information Published in: STAR Protocols License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.xpro.2022.101613